Confessions of a young novelist - Eco, Umberto (The Richard Ellmann lectures in modern literature, 2011)
Umberto Eco, author of "The Name of the Rose," looks back on his long career as a theorist and his more recent work as a novelist, and explores their fruitful conjunction.